Self‐Powered Wireless Sensor Node Enabled by an Aerosol‐Deposited PZT Flexible Energy Harvester. Issue 13 (9th May 2016) - Hwang, Geon‐Tae; Annapureddy, Venkateswarlu; Han, Jae Hyun; Joe, Daniel J.; Baek, Changyeon; Park, Dae Yong; Kim, Dong Hyun; Park, Jung Hwan; Jeong, Chang Kyu; Park, Kwi‐Il; Choi, Jong‐Jin; Kim, Do Kyung; et al.
Abstract : A flexible piezoelectric energy harvester was demonstrated by an aerosol‐deposited PZT film to realize a self‐powered wireless sensor node system. The flexible harvesting device can generate a voltage of 200 V and a current of 35 μA. A self‐powered wireless sensor node was constructed by integrating the PZT harvester, a rectifying/storage circuit, and a wireless temperature‐sensor node to measure ambient temperature and wirelessly transmit the data to a monitor.